(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The notion of "Viksit Bharat" (developed India) embodies development and growth, and "The White Paper on Indian Economy: A Reflection of Viksit Bharat" explores the many facets of India’s economic environment. In order to explain the difficulties encountered and the tactics used to attain sustainable development, the study critically analyzes important industries, including infrastructure, services, agriculture, industry, and social welfare. Outlining significant events, changes in policy, and international forces that have influenced India’s current economic structure, the booklet charts the country’s economic development historically. Analyzing their effects on India’s economic trajectory and competitive stance in the global economy, it dives into the demographic dividend, technological breakthroughs, and globalization trends. The White Paper also examines the ways in which inclusive growth, entrepreneurship, and competitiveness are fostered by government policies, regulatory frameworks, and institutional changes. It also discusses climate resilience, energy security, and environmental sustainability as essential elements of India’s economic strategy in light of international issues like resource constraints and climate change. In order to realize India’s aspirations of becoming a global economic powerhouse while ensuring equitable and sustainable growth for all of its citizens, the paper concludes by presenting a holistic perspective on Viksit Bharat and highlighting the imperatives of balanced and inclusive development, leveraging innovation and technology, fostering global partnerships, and nurturing human capital.